2017
DOI: 10.1159/000479584
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Aphasia following Right Temporal Lobectomy as Treatment of Recurrent Super-Refractory Status Epilepticus

Abstract: Background: Super-refractory status epilepticus (SRSE) is a critical neurological condition with a high mortality rate. There are only limited data to direct the treatment in SRSE, and surgery has been reported to successfully stop SRSE. We present a case of recurrent SRSE treated with urgent right temporal lobectomy in a right-handed woman which potentially saved her life but resulted in crossed sensory aphasia. Case Description: A 61-year-old woman with a recent episode of prolonged focal SRSE due to right f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…In both patients, the EEG findings during SRSE, that is, the "ictal" EEG findings, were the most useful for the preoperative identification of the epileptogenic region, confirming the previous reports. [7,17] In Patient 1, LPD was observed in the left frontotemporal region, and in Patient 2, repeated ictal discharges were consistently observed in the medial part of the left frontal region during the three SRSEs. Furthermore, in Patient 2, a high signal on DWI and focal hypermetabolism on FDG-PET were observed at the site corresponding to the ictal EEG findings.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In both patients, the EEG findings during SRSE, that is, the "ictal" EEG findings, were the most useful for the preoperative identification of the epileptogenic region, confirming the previous reports. [7,17] In Patient 1, LPD was observed in the left frontotemporal region, and in Patient 2, repeated ictal discharges were consistently observed in the medial part of the left frontal region during the three SRSEs. Furthermore, in Patient 2, a high signal on DWI and focal hypermetabolism on FDG-PET were observed at the site corresponding to the ictal EEG findings.…”
Section: Discussionmentioning
confidence: 93%
“…[9] However, the actuality and usefulness of focal resection surgery have not been fully clarified, as limited reports are available. [4,7,9,17] We treated two SRSE patients who underwent resection surgery and obtained good seizure outcomes. Herein, we retrospectively analyze the clinical findings of these patients and discuss the usefulness of resection surgery for SRSE.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 81 studies in the literature that met the inclusion criteria, 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 …”
Section: Resultsunclassified
“…Of the 81 studies in the literature that met the inclusion criteria, 13–92 the majority (60) reported only one patient. The remaining studies characterized a variable number of patients, ranging from 2 to 20.…”
Section: Resultsmentioning
confidence: 99%